2022
DOI: 10.3390/v14092027
|View full text |Cite
|
Sign up to set email alerts
|

Wild Bird Surveillance in the Gauteng Province of South Africa during the High-Risk Period for Highly Pathogenic Avian Influenza Virus Introduction

Abstract: Migratory birds carried clade 2.3.4.4B H5Nx highly pathogenic avian influenza (HPAI) viruses to South Africa in 2017, 2018 and 2021, where the Gauteng Province is a high-risk zone for virus introduction. Here, we combined environmental faecal sampling with sensitive rRT-PCR methods and direct Ion Torrent sequencing to survey wild populations between February and May 2022. An overall IAV incidence of 42.92% (100/231) in water bird faecal swab pools or swabs from moribund or dead European White Storks (Ciconia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…These birds feed on crickets, earthworms, beetles, amphibians, and other insects, which are abundant in the Hadejia‐Nguru wetlands, which is a wintering site for the Eurasian migrants. The detection of the AIV H5N1 subtype belonging to clade 2.2.3.4b in white stork species is consistent with the report by Abolnik et al 4 who also detected AIV clade 2.3.4.4b among moribund white stork in South Africa. Infections in this species have been repeatability reported also in Europe suggesting that white stork could spread the virus along its migratory route 37 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These birds feed on crickets, earthworms, beetles, amphibians, and other insects, which are abundant in the Hadejia‐Nguru wetlands, which is a wintering site for the Eurasian migrants. The detection of the AIV H5N1 subtype belonging to clade 2.2.3.4b in white stork species is consistent with the report by Abolnik et al 4 who also detected AIV clade 2.3.4.4b among moribund white stork in South Africa. Infections in this species have been repeatability reported also in Europe suggesting that white stork could spread the virus along its migratory route 37 …”
Section: Discussionsupporting
confidence: 92%
“…Ecologically, wetlands are very important habitats for birds as they utilize the resources for feeding, breeding, foraging, and resting 1 . The seasonal long‐distance migration of wild birds from Europe to Africa along the Western Siberian‐Mediterranean‐West Africa flyway during winter and the subsequent stopover at the wetlands plays an important role in the introduction of highly pathogenic avian influenza virus (HPAI) to the African region 2–4 . In Nigeria, several coastal and inland wetlands serve as congregation sites for both migratory and resident waterfowl.…”
Section: Introductionmentioning
confidence: 99%
“…The HA genes in this study harbor multiple basic amino acids at their cleavage site PLREKRRKR/GLF (Table 2), similar to H5N1 of clade 2.3.4.4 found in West Africa and Europe in 2021-2022, demonstrating a highly pathogenic form [51,52]. The receptor binding sites of the HA protein of Egyptian H5N1 in this study revealed amino acids Q222, and G224 (H5 numbering), suggesting an avian-like α2,3-sialic acid receptor binding preference [53,54].…”
Section: Genetic Characterization Revealed Close Related Features To ...supporting
confidence: 58%
“…Oropharyngeal, tracheal, cloacal and organ swabs or tissues were collected by veterinarians, animal health technicians and researchers from suspected clinical cases in sick and dead wild birds and poultry, across South Africa between April 2021 and December 2022. Samples were collected as part of passive government disease surveillance, active surveillance in African penguins, environmental fecal sampling of wild ducks [ 17 ], and a disease surveillance project at a seabird rehabilitation center. Active surveillance and rehabilitation center samples were collected into viral transport medium (VTM) comprising brain heart infusion (BHI) broth (pH 7.2) (Oxoid Ltd., Basingstoke, UK), 10% ( v / v ) glycerol and the following antimicrobials per liter: 100 mg doxycycline (Mylan, Potters Bar, UK), 100 mg enrofloxacin (Cipla, Beckenham, UK), 1000 mg penicillin-streptomycin (Sigma-Aldrich, Merck, Sofia, Bulgaria), and 5 mg amphotericin B (Bristol–Myers Squibb, Denham, UK).…”
Section: Methodsmentioning
confidence: 99%